2019
DOI: 10.2355/isijinternational.isijint-2018-788
|View full text |Cite
|
Sign up to set email alerts
|

Production of High-Strength Coke from Low-Quality Coals Chemically Modified with Thermoplastic Components

Abstract: In order to produce high-strength coke from low-quality coals, noncovalent bonds between O-functional groups in coal were cleaved by pyridine containing HPC pyridine soluble and HPC-derived thermoplastic components were introduced into the pores formed by swelling; thus, the synergistic effect during carbonization of the suppression of cross-linking reactions and the fluidity amplification due to close placement of coal and thermoplastic components was investigated. When HPC was extracted with pyridine, a decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…As is well-known, although HPC consists of hundreds to thousands of molecular weights, 18) HPC pyridine soluble is composed with lower molecular weight than original HPC, because DTG curve of the soluble gave the main peaks at around 250 and 450°C (HPC also provides the main peaks at same temperatures), and the former peak does not observed for HPC pyridine insoluble. 5) In addition, it was found that the interaction of HPC pyridine soluble and coal occurs during heat treatment of chemically loaded coal prepared by this method. Now, although we cannot obtain the direct evidence of HPC pyridine soluble introduced into coal structure produced during solvent swelling, the lighter component in the prepared HPC pyridine soluble may be loaded into coal structure.…”
Section: Preparation Of Coal With Chemically-loaded Hpcmentioning
confidence: 93%
See 3 more Smart Citations
“…As is well-known, although HPC consists of hundreds to thousands of molecular weights, 18) HPC pyridine soluble is composed with lower molecular weight than original HPC, because DTG curve of the soluble gave the main peaks at around 250 and 450°C (HPC also provides the main peaks at same temperatures), and the former peak does not observed for HPC pyridine insoluble. 5) In addition, it was found that the interaction of HPC pyridine soluble and coal occurs during heat treatment of chemically loaded coal prepared by this method. Now, although we cannot obtain the direct evidence of HPC pyridine soluble introduced into coal structure produced during solvent swelling, the lighter component in the prepared HPC pyridine soluble may be loaded into coal structure.…”
Section: Preparation Of Coal With Chemically-loaded Hpcmentioning
confidence: 93%
“…In particular, it was demonstrated that coke manufactured from a specially-prepared input material -in which pyridine-soluble HPC components are chemically loaded into the coal pores produced by pyridine treatmentis stronger than that produced from the unloaded raw coal. 5) This result was attributed to a synergistic interplay of two mechanisms: (a) pyridine-induced cleavage of noncovalent bonds between O-functional groups in coal, and (b) suppression of cross-linking reactions during carbonization, and amplification of fluidity due to increased proximity between coal and thermoplastic components, resulting from the introduction of HPC-derived thermoplastic components into the pores produced by pyridine-induced swelling.…”
Section: Influence Of Heating Conditions On the Strength Of Coke Prodmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, we demonstrated that coke manufactured from a specially-prepared input material -in which HPC pyridine-soluble components are chemically-loaded into the pores produced by pyridine treatment of coal -is stronger than that produced from the unloaded input material. 8,9) We attributed this result to a synergistic interplay of two mechanisms: (a) pyridine-induced cleavage of noncovalent bonds between O-functional groups in coal, and (b) suppression of cross-linking reactions during carbonization and amplification of fluidity due to increased proximity between coal and thermoplastic components, resulting from the introduction of HPC-derived thermoplastic components into the pores produced by pyridine-induced swelling. 8,9) In addition, we showed that the extent of the improvement in strength is greater for formed coke.…”
Section: Introductionmentioning
confidence: 99%